Differentiation Between Eosinophilic Otitis Media and Otitis Media Associated With Eosinophilic Granulomatosis With Polyangiitis. Issue 8 (September 2019) - Fukuda, Atsushi; Morita, Shinya; Nakamaru, Yuji; Hoshino, Kimiko; Fujiwara, Keishi; Homma, Akihiro
Abstract : Objective: To perform comparisons and clarify differences in clinical manifestations between eosinophilic otitis media (EOM) and otitis media associated with eosinophilic granulomatosis with polyangiitis (EGPA). Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Twenty-two ears of 11 patients exhibiting EOM (EOM group) and 20 ears of 12 patients exhibiting otitis media associated with EGPA (EGPA group). Main Outcome Measures: Otological manifestations, nasal and paranasal manifestations, incidence of asthma, positivity for serum antineutrophil cytoplasmic antibodies (ANCA), total serum immunoglobulin (Ig) E level, peripheral blood eosinophil fraction, and hearing outcomes. Results: The incidence and age of onset of asthma and chronic rhinosinusitis were comparable between the EOM and EGPA groups. Moreover, otological findings and hearing outcomes at the initial visit were similar in both groups. Computed tomography images of the paranasal sinus showed predominant opacification of the ethmoid sinus in both groups. Although the total serum IgE level was not significantly different, the peripheral blood eosinophil fraction was significantly larger in the EGPA group than in the EOM group ( p  = 0.0035). Furthermore, the rate of myeloperoxidase–antineutrophil cytoplasmic antibodies (ANCA) positivity was significantly higher in the EGPA group than in the EOM group ( p  = 0.019). Conclusions: The findings of the present study suggest that the phenotypic characteristics of EOM closely resemble those of otitis media associated with EGPA in early stages before the appearance of vasculitis. Therefore, it is challenging to differentiate the two conditions purely on the basis of otorhinological examinations.